Cardiovascular risk in middle-aged breast cancer survivors: a comparison between two risk models - Érika Pereira de Sousa-; Délio Marques Conde; Lúcia Costa-Paiva; Edson Zangiacomi Martinez; Aarão Mendes Pinto-Neto (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2014)
PURPOSE: It was to assess the risk of cardiovascular disease (CVD) in breast cancer survivors (BCS).METHODS: This cross-sectional study analyzed 67 BCS, aged 45 -65 years, who underwent complete oncological treatment, but had not received hormone therapy, tamoxifen or aromatase inhibitors during the previous 6 months. Lipid profile and CVD risk were evaluated, the latter using the Framingham and Systematic COronary Risk Evaluation (SCORE) models. The agreement between cardiovascular risk models was analyzed by calculating a kappa coefficient and its 95% confidence interval (CI).RESULTS: Mean subject age was 53.2±6.0 years, with rates of obesity, hypertension, and dyslipidemia of 25, 34 and 90%, respectively. The most frequent lipid abnormalities were high total cholesterol (70%), high LDL-C (51%) and high non-HDL-C (48%) concentrations. Based on the Framingham score, 22% of the participants had a high risk for coronary artery disease. According to the SCORE model, 100 and 93% of the participants were at low risk for fatal CVD in populations at low and high risk, respectively, for CVD. The agreement between the Framingham and SCORE risk models was poor (kappa: 0.1; 95%CI 0.01 -0.2) for populations at high risk for CVD.CONCLUSIONS: These findings indicate the need to include lipid profile and CVD risk assessment in the follow-up of BCS, focusing on adequate control of serum lipid concentrations.